Antecedents of entrepreneurial intentions and behaviour: The role of entrepreneurial education and contextual factors / Tariq Ahmed - Tariq, Ahmed (2015)

(untitled)
Given the important role of entrepreneurship, understanding and predicting the emergence of venture initiation entails a research to explore the antecedents of entrepreneurial intention and behaviour. Review of past literatures has revealed that a research gap exists mainly in the conceptualization of the framework, particularly in examining the role of exogenous factors (entrepreneurship education), contextual and environmental factors (perceived entrepreneurial motivators and barriers) in developing entrepreneurial intentions and behaviour among the university graduates. Indeed, none of the past studies accounts for the moderating role of contextual and environmental factors in the development process of entrepreneurial intention and behaviour. This research develops and proposes a theoretical model of the antecedents of entrepreneurial behaviour, drawing together the different strands of thoughts and research on the role that formal entrepreneurship programmes may (or may not) play in influencing entrepreneurial attitude and consequently, intention and behaviour. As a whole, the main objective of this study was to investigate the link between entrepreneurial education, attitude, intention and behaviour. The three specific objectives of the study were: I) to examine the effect of entrepreneurship education programmes on the entrepreneurial attitude and intentions of university graduates, II) to assess the effect of the benefits of entrepreneurship education programme that raises the entrepreneurial attitude and intentions of university graduates, 3) to investigate the moderating effect of perceived contextual and environmental motivators and barriers on the relationship between entrepreneurial intention and behaviour. The data for the study was collected from university graduates who are enrolled in entrepreneurship education programmes. Survey questionnaires were distributed to the iv graduates during the class and were asked to provide data pertaining to the important constructs of the study. Structural equation modelling was applied to examine the measurement model, structural model as well as to test the hypothesis of the study. Overall, the entrepreneurship education programmes are found to have a positive influence on the entrepreneurial attitude of graduates and as a result, these students attain strong entrepreneurial intentions. Furthermore, within the entrepreneurship education programme, entrepreneurship learning benefits are found to be the most influential dimension in founding the entrepreneurial attitude of the students. In addition, inspiration and utilization of incubation resources are also found to positively affect subjective norms and perceived behaviour control, thus exhibiting its influence in establishing the entrepreneurial intention of the graduates. Moreover, the moderating effect of perceived entrepreneurial motivators and barriers were analysed to examine its relationship between entrepreneurial intention and behaviour. The students are found to be deterred and influenced by perceived entrepreneurial environmental barriers. The main conclusion drawn from this study is a better understanding of the entrepreneurship education programmes, especially knowing the perceived benefits and its influence on entrepreneurial intentions and behaviour. This study enables us to identify the sequence of influences and the important effects of each dimension of entrepreneurship programme on entrepreneurial intentions independently. More importantly, the study shows that the effectiveness of entrepreneurship education programme is subjected to contextual factors, particularly entrepreneurial environment and context. As such, designated entrepreneurship education should consider the environmental context.